2016
DOI: 10.1130/ges01293.1
|View full text |Cite
|
Sign up to set email alerts
|

Anatexis, cooling, and kinematics during orogenesis: Miocene development of the Himalayan metamorphic core, east-central Nepal

Abstract: The exposed mid-crustal rocks of the Himalayan orogen provide a natural laboratory for constructing the kinematic evolution of the midcrust during a large-scale continental collision. Kinematic models provide testable, geometrically valid, internally consistent, integrated solutions for diverse geological data from deformed regions. We investigated the Tama Kosi region of east-central Nepal with structural, geochemical, and geochrono logical methods to refine a detailed kinematic model for the Miocene Epoch, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 72 publications
2
17
0
Order By: Relevance
“…In this scenario, out‐of‐sequence deformation brought northern and structurally deeper GHS rocks to their current position, such that the two regions represent significantly different across‐strike positions in the middle crust, despite their geographical proximity. Out‐of‐sequence thrusting isolating foreland metamorphic rocks has also been suggested north of the Kathmandu klippe in central Nepal (Figure a; Johnson et al, ; Larson et al, ), in far‐eastern Nepal (Figure a; Schelling & Arita, ), in Bhutan (Figure a; Grujic et al, , ; Kellett et al, ; Warren et al, ), and in Arunachal Pradesh (Figure a; Warren et al, ). Out‐of‐sequence thrusting of hinterland GHS on top of foreland GHS is also predicted by thermal‐mechanical numerical models containing an embedded weak upper layer in the upper crust (e.g., model HT‐111; Jamieson et al, ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this scenario, out‐of‐sequence deformation brought northern and structurally deeper GHS rocks to their current position, such that the two regions represent significantly different across‐strike positions in the middle crust, despite their geographical proximity. Out‐of‐sequence thrusting isolating foreland metamorphic rocks has also been suggested north of the Kathmandu klippe in central Nepal (Figure a; Johnson et al, ; Larson et al, ), in far‐eastern Nepal (Figure a; Schelling & Arita, ), in Bhutan (Figure a; Grujic et al, , ; Kellett et al, ; Warren et al, ), and in Arunachal Pradesh (Figure a; Warren et al, ). Out‐of‐sequence thrusting of hinterland GHS on top of foreland GHS is also predicted by thermal‐mechanical numerical models containing an embedded weak upper layer in the upper crust (e.g., model HT‐111; Jamieson et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…Black polygon in the Karnali klippe indicates the map area of Figure . The locations of other areas relevant to this study are indicated by circled numbers: 1—Dadeldhura klippe (Antolín et al, ); 2—Gurla Mandhata (Murphy & Copeland, ); 3—Humla Karnali (Braden et al, ; Yakymchuk, ); 4—Dolpo synclinorium (Cannon & Murphy, ); 5—Mugu Karnali (Iaccarino, Montomoli, Carosi, Massonne, & Visonà, ; Montomoli et al, ); 6—Lower Dolpo (Carosi et al, , ; Gibson et al, ); 7—Annapurna (Brown & Nazarchuk, 1993; Godin, ; Godin, Brown, & Hanmer, ; Hurtado et al, ); 8—Jajarkot klippe (Soucy La Roche et al, ); 9—Kathmandu klippe (Johnson et al, ; Larson et al, ); 10—Ama Drime (Groppo et al, ; Kellett et al, ); 11—far‐eastern Nepal (Schelling & Arita, ); 12— Bhutan (Grujic et al, , ; Kellett et al, ; Warren et al, ); 13—Arunachal Pradesh (Warren et al, ). (b) Cross section A‐A′ illustrating the relationship between the GHS in the homoclinal slab and the GHS in the Karnali klippe (modified from Soucy La Roche et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…16 to ca. 12 Ma (e.g., Carrapa et al, 2016;Kellett et al, 2013), and to the south a contemporaneous outof-sequence thrust system occurs (e.g., Grujic et al, 2011;Larson et al, 2016). The apparently restricted range of these systems could indicate that they respond to the relatively large magnitude burial and subsequent uplift associated with the final slab detachment, as in the Chemenda group modeling.…”
Section: Comparisons Of the Slab Dynamics Model To Prior Modelsmentioning
confidence: 96%
“…Where identified, these structures typically occur as either late Oligocene to early Miocene reverse sense shear zones that drive metamorphism in the overridden footwall [ Montomoli et al ., , ] or as postpeak metamorphic, middle to late Miocene out‐of‐sequence structures [ Grujic et al ., ; Warren et al ., , ]. While most of the observed structures are related to deformational processes that occurred during the assembly and/or initial exhumation of the middle crust [ Larson et al ., ; Cottle et al , ], there is some indication that ductile deformation associated with these faults and other major structures in the Himalaya may have occurred at temperatures as low as ~450–500°C [ Law et al ., ; Larson and Cottle , ; Larson et al ., ]. Such temperatures approach the effective range of common mineral thermochronometers.…”
Section: Introductionmentioning
confidence: 99%